Sedimentation Rate in Sub River Flows Musi PLTA Intake Area - M. Edi Armanto; Taufik Ari Gunawan; Elisa Wildayana; Azhadi Mutaqin (Sriwijaya Journal of Environment, 2023)
The quality of a watershed can be seen from the discharge of the river flow. Watershed quality can also be seen from the sedimentation found in river water flows and river bodies. Sedimentation is sediment produced by the erosion process carried by the flow and deposited in a place where the water velocity is smaller than the settling velocity. This research was conducted in the intake area of the Musi Hydroelectric Watershed, Ujan Mas District, Kepahiang Regency, Bengkulu Province in August – October 2022. This study used hydrographic and bathymetric survey methods. The results of research on sedimentation using bathymetric maps and the results of sub- bottom profiling in the intake corridor area of the Musi Hydroelectric Power Plant (up to approximately 500 m from the weir), it is known that an average thickness of 1.7 meters near the intake pond (south side) and is getting higher up to 2.5 meters thick to the north or upstream of the river. The thickness of the sediment tends to thicken towards the east or along the riverbank with an average thickness of 2 meters, while in the west it tends to be thinner, with an average of 1.8–2.0 meters. Based on the results of the grab sampler, the type of sediment layer is sandy silt.